Engineered Nanoparticles for Wastewater Treatment System - Tara Hafiz Rayhan; Chi Nam Yap; Arma Yulisa; Rubiyatno; Irina Popescu; Jose Arturo Alvarez; Risky Ayu Kristanti (Tecno Scientifica Publishing, 2022)
Industrial and commercial use of engineered nanoparticles is rising. Less care is given to the negative effects on the environment and wastewater treatment systems, which could release hazardous pathogens and microorganisms and threaten human health. Due to their size and features, artificial nanoparticles can easily enter wastewater systems and impair treatment. This paper aimed to focus on nanoparticle detection limitations and their effects on wastewater treatment technologies. Nanoparticles have the potential to be utilised in the treatment of waste water. By virtue of its exceptionally high surface area, it can effectively remove poisonous metal ions, microorganisms that cause disease, as well as organic and inorganic solutes from water. Various groups of nanomaterials, such as metal-containing nanoparticles, carbonaceous nanomaterials, zeolites, and dendrimers, have been demonstrated to be effective for water purification. Composites are two or more materials assembled synthetically. Nanocomposites are vital for environmental rehabilitation because pollution is one of the world's biggest concerns and polluted water management. Population growth has increased the need for clean water. This includes ceramics, metal-based polymers, carbon, and iron-based graphene. Nanocomposites such as carboxyl methyl may adsorb a heavy metal ion and pesticide at a satisfactory rate. This study found that nanocomposites are good for restoring the environment and can be used in countries with low incomes.